Validation of a multi-scale simulation strategy based on the Pointwise Strain Superposition Method. Issue 1 (February 2021) - Moda, M; Monelli, B D; Benassi, M; Palladino, M
Abstract: This paper details the experimental validation of a multi-scale simulation strategy that we developed for predicting the stresses and distortions induced by Powder Bed Fusion processes. The strategy comprises a meso-scale model, a macro-scale model, and a scaling method named Pointwise Strain Superposition. The first model evaluates the temperature, stress, and strain fields produced by a single scan line. The scaling method transfers the meso-scale results to the macro-scale model, which is then able to simulate the entire manufacturing process with a reasonable computational cost. The simulation strategy was validated by comparing its results with the stresses and distortions measured on several specimens made of selective laser melted Inconel 718. Stresses were measured through the blind hole drilling method on a cylindrical specimen printed with two different scanning strategies, while distortions were measured on a hollow cylinder and on a cantilever-shaped specimen after removing its supports. In both cases the simulation showed first- or higher-order accuracy despite the significant uncertainties regarding the input parameters and material properties. This robustness, coupled with its computational efficiency, leads us to believe that our simulation strategy could enhance the process optimization and provide a better understanding of the underlying physical phenomena along with their effects on the manufactured parts.